Design of a special-purpose airfoil for smaller-capacity straight-bladed VAWT - Islam, Mazharul; Ting, David S-K; Fartaj, Amir (SAGE Publications, 2007)
Selection of airfoil is one of the most critical factors in achieving better aerodynamic performance and in determining the optimum dimensions of a fixed-pitch straight-bladed Darrieus type vertical axis wind turbine (SB-VAWT), along with solidity, radial arm parasitic drag, aspect ratio etc. Airfoil related design changes also have the potential for increasing the cost effectiveness of SB-VAWTs which is one of the simplest types of wind turbine and they are prospective candidate for diversified urbartand rural applications. After identifying the main aerodynamic challenges of this type of wind turbine, the authors short listed the salient aerodynamic and geometric characteristics of a desirable airfoil for a self-starting and better performing SB-VAWT. Based on these findings, detailed, performance analyses were done with several prospective airfoils. Finally a special-purpose airfoil has been designed for smaller capacity SB-VAWT.